Pelatihan Digital Marketing Ibu Rumah Tangga Pelaku Usaha Mikro Di Kelurahan Pojok Kota Kediri - Forijati, Rr.; Sugiono, Sugiono; Anas, M.; Muchson, Mochamad; Subagyo, Subagyo; Winarsih, Tri (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2022)
One of the roles of housewives in strengthening the economy is to open a business so that their household needs are fulfilled. However, business management that has been carried out so far is in a simple way, so efforts are needed on how to market their products so that they can survive in trade competition. The purpose of this service is to provide digital marketing training for housewives with training methods and accompanied by product photography training. Then the results that can be taken show that the potential of housewives actually has an influence on the household economy so that it is maintained. Digital marketing training for housewives in the Corner Village of Kediri is expected to help housewives who have businesses in optimizing technology and media to facilitate business in helping the economy, especially during the COVID-19 pandemic.